SCABIES : PENYEBAB, PENANGANAN DAN PENCEGAHANNYA - Griana, Tias Pramesti (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2013)
Gudik or kudis is a kind of skin disease that could be found in people who living in crowded neighborhood, for examples slums area, Islamic boarding school, prison, military camp and hospital. Gudik could be infect all age, race, and social economic level. Many people do not know that the cause of gudik is mite which named Sarcoptes scabiei. According to Departemen Kesehatan Republik Indonesia, scabies ranked third of the twelve of skin disease that most often arises. Until now, scabies is still neglected, and it becomes to be public health problems worldwide. As the transmission process is fast, misunderstanding of society about this disease makes difficult to eradicate scabies. Sarcoptes scabiei lives in stratum corneum of skin and eat cell fluids. Female mite digs tunnels under skin surfaces and lays its eggs. This mite activities cause rash on the skin and itch at night. Transmission of scabies can through direct or indirect contact with the patient. Drug of choice for scabies is still debatable. Although the results of therapy are effective, sulfur 5%-10%, benzyl benzoate, crotamiton 10%, permethrin 5% and ivermectin give bad side effect for patient. In vitro study showed the effectivity of tea tree 5% (Melaleuca alternifolia), paste of neem leaves (Azadirachta indica) and turmeric (Curcuma longa),Â and anise (Pimpinella anisum) as scabicide. Prevention of scabies transmisstion is carried out by hygiene and treatment for all people who have direct contact with the patient.